Sorry I am a little late...
a = -2
b = -9
Here is how to solve the problem.
First thing I did was multiply the first equation by -2 so that we can eliminate the the b. After you multiply it by -2, your new equation is -16a + 8b = -40.
You leave the second equation alone and all you do is combine like terms. So -16a+5a is -11. And you eliminate the b. Then you're going to do -40+62 which is 22. So it's -11a=22 and then you have to solve for a. What I did was I multiplied the whole thing by minus to turn the a positive. So then it's 11a=-22. Pretty easy, the final step is to simplify. -22/11 is -2. ;D
So there you have your first answer.
a = -2
Now we're going to use the first answer to help us find b.
For the second equation, all you're going to do is plug in that a.
5 (-2)-8b=62
-10 - 8b = 62
Now we move the -10 to the other side...
-8b = 62 + 10
-8b = 72
Multiply the whole thing by negative once again to turn the b positive.
Now we have 8b = -72
The final step is to simplify. -72/11 = -9
b = -9
Hope this makes sense! Also I had the same question on my test and I got it right. :)
Answer:
Alright so on this type of problem you just perform the operation they ask for, which in this case is subtraction.
Your first step will be to set up the problem:
f(x) - g(x)
Next you will substitute in your values:
(2x + 1) - (x2 - 7)
The easiest way to do the subtraction problems is to distribute your negative into your second set of parenthesis, so your expression would become:
2x + 1 - x2 + 7
Then combine your like terms:
2x - x2 + 8
Lastly put your expression in standard form (highest exponent to lowest)
-x2 + 2x + 8
Hope this helped!
Step-by-step explanation:
Cancel y values
multiply 2nd equation by 4 and add to first
-9x+4y=8
<u>-12x-4y=16 +</u>
-21x+0y=24
-21x=24
divide both sides by -21
x=24/-21
x=-8/7
C is answer
Hijjsjjsjaamakkansnnaksjjfjfg